Kinerja dan Kemandirian Keuangan Daerah Kabupaten Ciamis dan Kabupaten Tasikmalaya Tahun 2005 dan 2006 - Irma Kusumawardani; Sukiman Sukiman; Neni Widayaningsih (EKO-REGIONAL, 2008)
The purposes of this research are to analyze how regional government optimizes their regional financial and its influence to the increasing level of Domestic Product Regional Bruto, and also to analyze the independency level in Ciamis and Tasikmalaya Region. The method analysis used in this research are Regional Independency Model (RFIR and four regional Independency model by LPEM FEUI team model) and Harmonizing Ratio that consist of DER (Development Expenditure Ratio) and RER (Routine Expenditure Ratio).According to analysis result of Development Expenditure Ratio (DER) and Routine Expenditure Ratio (RER), it notified that Ciamis and Tasikmalaya region tends to be increase in the term of development expenditure and decrease in the term of routine expenditure. But in the term of those development fund allocation notified that it have not prioritized in potential sectors is the potential sector in Domestic Product Regional Bruto. Agriculture, Trade and Service sector is the potential sector in Domestic Product Regional Bruto but only accept less than ten percent total of regional development expenditure. This research implies that, for the next period is still need effort to improve the sources of acceptance from Regional Origin Income by intensification and extensification of Regional Origin Income. Beside that, to improve the capability of region independency can be done by developing and improving regional potencies. Both of region also have to regulate the developing expenditure allocation so that the budget can be allocated to the potential sectors for the Domestic Product Regional Bruto growth, so it can stimulate the growth improvement of Regional Origin Income.Keywords: Regional Independency Model, Harmonizing Ratio, Domestic Product Regional Bruto